Designing bandpass filters in 8 – 14 μm range for Si and Ge substrates - Asghar, M.H.; Khan, M.B.; Naseem, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Modular bandpass spectral filter for germanium and silicon substrates in 8 – 14 μm band applications have been proposed. The design approach, similar to antireflection coating design has been adopted to make the model simple with lesser number of layers. The full width half maximum (FWHM) value of the filter for the two substrates is varied by varying the refractive index of a single layer in the multilayer stack. The design is also analyzed for zero and 45 degree angles of incidence. The analysis has shown that the designed configuration exhibits identical behavior for these two substrates. The proposed configuration could be used for different optical and optoelectronic applications.